Examination of the levels of structures in the thorax in multidetector computerized tomography images - Bolatlı, Güneş; Ünver, Nadire; Koplay, Mustafa; Fazlıoğulları, Zeliha; Karabulut, Ahmet Kağan (Journal of Surgery and Medicine, 2020)
Aim: Levels of the anatomical structures found in thorax and their relationships are particularly important in terms of surgical procedures. These levels are indicated with reference to the ribs and most are based on cadaver studies. The vertebral level of many structures is not specified. In this study, it was aimed to determine the level changes of some structures in the thorax according to age and gender by referring to the vertebrae. Methods: Multidetector computed tomography images of the thorax region in the PACS archives of Selcuk University Medical Faculty Hospital were used in the study. Images of 700 people, who did not undergo thoracic surgery, were studied in different age groups. The anatomical structures were evaluated with reference to the vertebrae on these images, and the findings were compared according to age groups and genders. Results: Some of the levels of the investigations were different from the information in the classical books. It was seen that the entrance level of the aorta from the diaphragm was at Th10 level, the entrance level of superior vena cava to the right atrium was Th7 in the 0-9-year age group, Th6 level in the other age groups, and exit level of the pulmonary trunk from the right ventricle and the apex of the heart were Th7 and Th10, respectively. Conclusion: Most of our current knowledge is based on cadaver studies rather than living human beings and the intercostal spaces are referenced in defining the levels of structures in the thorax. Age and gender distinctions have not been made in cases where most of the structures are not specified. Vertebral reference is important in terms of comparing superficial and deep structures. As the thoracic surgeon is needed in every age group, it is important that surgeons know these differences